Intramuscular Lipoma of the Sternocleidomastoid Muscle: A Rare Entity Revisited - Jad Hosri; Yara Yammine; Nadine El Hadi; Jessica Aoun; Marc Mourad; Usamah Hadi (SAGE Publishing, 2024)
Intramuscular lipomas, typically found in subcutaneous tissue, rarely affect deeper muscular planes, especially those of the head and neck region. The following are 3 cases of intramuscular lipomas involving the sternocleidomastoid muscle. The first 2 patients presented with painless, palpable masses confirmed by diagnostic imaging as well-circumscribed intramuscular lipomas. One was treated surgically, while the other was managed conservatively with monitoring and close follow-up. The third patient reported dysphagia associated with occasional dyspnea and mild pain. The mass was identified as infiltrative lipoma and was resected surgically. Complete tumor removal with no recurrence at 6 months was observed for the first and last cases. The second case was serially followed at 3 and 6 months with no interval changes. We report the largest case series on intramuscular lipomas of the sternocleidomastoid muscle to enhance our understanding of this rare entity.